Digital skills mentoring for online teaching and evaluation in the Industrial Engineering Faculty of the University of Málaga. Issue 1 (October 2021) - Lozano, M M; Martín, S; Herrera, M; Cano, M J; Sevilla, L
Abstract: COVID-19 pandemic has forced the usual face-to-face educative activities to change to e-learning processes. When the faculty has the necessary knowledge on digital skills this obligatory step becomes easier. Videoconferences, as synchronous communication tool and Learning Management Systems (LSM) allow to carry out the e-learning actuations. The University of Málaga has required to adapt its educative activities to e-learning processes due to the pandemic. To facilitate this change, a digital skill mentoring actuation has been implemented in all faculties of the University of Málaga. The digital skill actuations have been related with evaluation processes and with communication systems to development the teaching classes. In this work, the experience in the Faculty of Industrial Engineering of the University of Malaga, is exposed. The results obtained show that the previous LSM used by the University of Malaga facilitated the change to the e-learning process in the Faculty of Industrial Engineering.